Inhibitory killer cell immunoglobulin-like receptors strengthen CD8+ T cell–mediated control of HIV-1, HCV, and HTLV-1 - Boelen, Lies; Debebe, Bisrat; Silveira, Marcos [UNESP]; Salam, Arafa; Makinde, Julia; Roberts, Chrissy H.; Wang, Eddie C.Y.; Frater, John; Gilmour, Jill; Twigger, Katie; Ladell, Kristin; Miners, Kelly L.; et al. (American Association for the Advancement of Science (AAAS), 2018)
Killer cell immunoglobulin-like receptors (KIRs) are expressed predominantly on natural killer cells, where they play a key role in the regulation of innate immune responses. Recent studies show that inhibitory KIRs can also affect adaptive T cell–mediated immunity. In mice and in human T cells in vitro, inhibitory KIR ligation enhanced CD8+ T cell survival. To investigate the clinical relevance of these observations, we conducted an extensive immunogenetic analysis of multiple independent cohorts of HIV-1–, hepatitis C virus (HCV)–, and human T cell leukemia virus type 1 (HTLV-1)–infected individuals in conjunction with in vitro assays of T cell survival, analysis of ex vivo KIR expression, and mathematical modeling of host-virus dynamics. Our data suggest that functional engagement of inhibitory KIRs enhances the CD8+ T cell response against HIV-1, HCV, and HTLV-1 and is a significant determinant of clinical outcome in all three viral infections.